Authentic Assessment of Speaking Skills in Junior High School - Armita Ayu Sekarsari; Muamaroh Muamaroh; Mauly Halwat Hikmat (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Authentic assessment is a pivotal in teaching-learning process. With the use of authentic assessment, teachers can measure students’ learning achievement and progress effectively. This research investigated how teachers implement authentic assessment focusing in students’ speaking skills in two different schools. The study applied descriptive-qualitative method. Two English teachers were interviewed. In addition, the data collected by structured-interview and documentation. The finding stated that the English teachers applied authentic assessment nicely through the usage of different kind appealing activities in their speaking class.